The mechanism and kinetics of DTPA-promoted dissolution of barite - Putnis, Christine; Kowacz, M.; Putnis, Andrew (Pergamon, 2008)
The dissolution rate of natural barite, BaSO4, was measured in solutions of DTPA (diethylene triamine penta-acetic acid) to investigate the mechanism of ligand-promoted dissolution using a strong chelating agent. Experiments were carried out over a range of DTPA concentrations 0.5-0.0001 M solutions, at room temperature (22 °C), as well as a range of temperatures, 22-80 °C at 1 atm. The dissolution rate is inversely related to the DTPA concentration in solution. A more dilute DTPA solution is shown to be more efficient as a solvent in terms of the approach to the equilibrium saturation value for the dissolution of Ba2+. An analysis of the temperature dependence of the dissolution rate at high pH by the determination of activation energies indicates that the reaction is probably controlled by the pre-exponential term in the rate constant. This indicates that reaction frequency mostly controls differences in reactivity and suggests an explanation for the results in terms of stearic hindrance due to adsorbed DTPA molecules at the barite surface. The effect of DTPA on the solvation of the Ba2+ ion may also influence the dissolution rate. © 2008 Elsevier Ltd. All rights reserved.